2006
DOI: 10.1080/15287390600751371
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Ecotoxicity Study of Pharmaceuticals in the Marine Environment

Abstract: Environmental fates and effects of pharmaceuticals in the aquatic environment have been the focus of recent research in environmental ecotoxicology. Worldwide studies of common over-the-counter pharmaceuticals have reported detectable levels in the aquatic environment, but there are few studies examining impacts on marine habitats. These drugs can affect the functions of various vertebrates and invertebrates. The stability of two pharmaceuticals, cyclizine (CYC) and prochlorperazine (PCZ), in seawater was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Though PPCPs are present usually only at trace concentrations in the environment, questions are raised regarding chemical persistence, microbial resistance, and synergistic effects of the numerous PPCPs present (Daughton and Ternes 1999). Researchers examining the toxicological implications of PPCPs in the environment have found that these low concentrations can elicit adverse effects on aquatic life (Choong et al 2006;Crane et al 2006). These findings have engendered public concerns as to the possible effects the compounds may exert on both human health and waterway ecology (Ankley et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Though PPCPs are present usually only at trace concentrations in the environment, questions are raised regarding chemical persistence, microbial resistance, and synergistic effects of the numerous PPCPs present (Daughton and Ternes 1999). Researchers examining the toxicological implications of PPCPs in the environment have found that these low concentrations can elicit adverse effects on aquatic life (Choong et al 2006;Crane et al 2006). These findings have engendered public concerns as to the possible effects the compounds may exert on both human health and waterway ecology (Ankley et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…There is some evidence to suggest that the environmental fate of pharmaceuticals can differ between fresh and saline environments. The transformation behaviour of ibuprofen differed between freshwater and seawater [44] and prochlorperazine was more stable in seawater than freshwater [43].…”
Section: (E) Environmental Fate Of Pharmaceuticals In Marine Environmmentioning
confidence: 99%
“…Photodegradation may be a less important removal mechanism in coastal waters compared with more shallow freshwater environments due to light attenuation. Indirect photodegradation mechanisms may differ to those occurring in freshwater due to differences in water composition [42,43]. There is some evidence to suggest that the environmental fate of pharmaceuticals can differ between fresh and saline environments.…”
Section: (E) Environmental Fate Of Pharmaceuticals In Marine Environmmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutically active compounds (PhACs) were developed to target specific human physiological pathways [270]. After consumption, residual PhACs or/and their metabolites are excreted from human bodies into sewage systems.…”
Section: Introductionmentioning
confidence: 99%